How do gender and competition level influence the physical demands in worst-case scenarios of elite football referees? - Martinez-Torremocha, G.; Alonso-Callejo, A.; Sanchez-Sanchez, J.; Garcia-Unanue, J.; Gallardo, L.; Martin-Sanchez, M. L.; Serrano, C.; Felipe, J. L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The aim of this study was to describe and compare the physical demands in Worst-Case Scenarios (WCS) across different competition levels in male and female football of Spanish elite football referees during matches, comparing competitions independently for male and female referees.